The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5665/sleep.5742
|View full text |Cite
|
Sign up to set email alerts
|

Nonbenzodiazepine Sedative Hypnotics and Risk of Fall-Related Injury

Abstract: For the treatment of insomnia in older adults, eszopiclone may present a safer alternative to zolpidem, in terms of fall-related injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…Since it usually occurs during the transformation of body posture, this is also compatible with the circumstance of injurious falls occurred at the bedside in our study. The previous studies had pointed out that the risk of hip fracture was significantly increased in elderly patients with taking sedative-hypnotics, in line with our suggestions that sedative-hypnotics was associated with severe injuries such as fractures after falls [25] . The reason for that may be due to the side effects on the central nervous system, especially in the first few hours after taking the drugs easily leading to some adverse reactions such as drowsiness, fatigue, impaired balance and functions of cognitive and motor, especially in elderly patients [26,27] .…”
Section: Development Of the Predicting Nomogramsupporting
confidence: 89%
“…Since it usually occurs during the transformation of body posture, this is also compatible with the circumstance of injurious falls occurred at the bedside in our study. The previous studies had pointed out that the risk of hip fracture was significantly increased in elderly patients with taking sedative-hypnotics, in line with our suggestions that sedative-hypnotics was associated with severe injuries such as fractures after falls [25] . The reason for that may be due to the side effects on the central nervous system, especially in the first few hours after taking the drugs easily leading to some adverse reactions such as drowsiness, fatigue, impaired balance and functions of cognitive and motor, especially in elderly patients [26,27] .…”
Section: Development Of the Predicting Nomogramsupporting
confidence: 89%
“…Other notable results with respect to the negative impact of BZRAs include: Tom et al . (), who reported that use of zolpidem was associated with greater risk of hip fracture and traumatic brain injury than eszopiclone; Sun et al . () who demonstrated a significant relationship between zolpidem use and suicide attempts, as well as completed suicides; and Joya et al .…”
Section: Insomniamentioning
confidence: 99%
“…Generally, poorer sleep of the elderly may reflect degeneration of wake‐ and sleep‐promoting neurons in the brain (Mander, Winer, & Walker, ), as well as a phase‐advance of the sleep–wake system, which could potentially impact the efficacy of sleep treatments. The risk that the elderly may be more prone to nighttime and next‐day residual effects, particularly falls, with some existing sleep treatments is also a concern (Glass, Lanctot, Herrmann, Sproule, & Busto, ; Tom, Wickwire, Park, & Albrecht, ). Despite these concerns, few longer‐term (> 1 month) randomized controlled trials of sleep medications have been conducted in the elderly.…”
Section: Clinical Profile In the Elderlymentioning
confidence: 99%